Poverty distribution of different types of forest-related communities: Case study in Wan Abdul Rachman Forest Park and mangrove forest in Sidodadi Village, Lampung Province, Indonesia - ROMMY QURNIATI; ARIEF DARMAWAN; RIZKI BAHAGIA UTAMA; MAKOTO INOUE (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Qurniati R, Darmawan A, Utama RB, Inoue M. 2019. Poverty distribution of different types of forest-related communities: Case study in Wan Abdul Rachman Forest Park and mangrove forest in Sidodadi Village, Lampung Province, Indonesia. Biodiversitas 20: 3153-3163. Forest has important role in community because it can influence social characteristics as well as the quality of life of the household. In the tropics, many people living around forest are in poor conditions. Sidodadi Village of Pesawaran District, Lampung Province bordered to Wan Abdul Rachman (WAR) Forest Park in the upland and mangrove forest in the coastal area represents a good case study of communities living adjacent to forests with different ecosystem type. The research objective was to identify and analyze the characteristics and the level of household poverty of community living around two forested areas (i.e. upland forest in WAR Forest Park versus mangrove forest) in Sidodadi Village. In this village, households were interviewed by randomly selecting 215 respondents. The poverty was analyzed using five indicators, i.e. the economic characteristics, material wealth, health, infrastructure and services, and knowledge. The study found that base on the aggregated five poverty indicators there were no households categorized as poor. However, analyses in each indicator had diverse results. Based on the indicators of knowledge and economic characteristics, we found that most respondents were classified as poor while based on three other indicators there were classified as rich. The poor knowledge level was dominantly in older people who have low formal and informal education, while poverty in terms of economic characteristics due to limited opportunity to have better livelihood. Results also indicate that the poor households were located near mangrove forests while those classified as rich were located near upland forest in WAR Forest Park. The rich households had better opportunities to earn income from limited uses of forest in the upland area, yet similar opportunities were not obtained from mangrove forests. Sustainable use of mangrove forests should be considered to support the livelihood option of the surrounding community to enhance their wealth.